Makna Tradisi Penyampaian Famotu Ono Nihalo (Nasehat kepada Pengantin Perempuan) pada Pesta Pernikahan Adat Nias di Desa Lasarabaene Kecamatan Mandrehe Kabupaten Nias Barat - Yunano Waruwu; Masniar Sitorus; Sudirman Lase; Jupalman Welly Simbolon (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The Famotu Ono Nihalo tradition is one of the essential rituals in the customary wedding ceremonies of the Nias community, particularly in Lasarabaene Village, Mandrehe Subdistrict, West Nias Regency. This tradition consists of giving advice to the bride, which is rich in moral, spiritual, and social values. The ritual not only affirms the bride’s status as a wife but also serves as a medium for transmitting cultural values and collective identity. However, along with the wave of modernization, this tradition has undergone changes in terms of its form, symbolic meaning, and cultural values. This study aims to reveal the symbolic meanings contained in the Famotu Ono Nihalo ritual and to analyze the forms of social interaction within it, including its transformation due to social change. The research employs a descriptive qualitative method with data collected through observation, in-depth interviews, and documentation. The informants consist of traditional leaders, women elders, and community members who still practice and understand the tradition. The findings show that the white cloth symbolizes purity and blessing, while afo (betel quid) represents acceptance and social attachment. Although the ritual today tends to be simplified and some cultural symbols are no longer used, the core values such as parental advice, blessings, and the strengthening of social cohesion remain preserved. Therefore, Famotu Ono Nihalo continues to be relevant as a cultural heritage and a form of social education, even as it adapts to modern changes.